ChemInform Abstract: Rhodium‐Catalyzed Chemo‐ and Regioselective Cross‐Dimerization of Two Terminal Alkynes. Issue 28 (21st June 2013) - Xu, Hua‐Dong; Zhang, Ren‐Wei; Li, Xiaoxun; Huang, Suyu; Tang, Weiping; Hu, Wen‐Hao
Abstract Dimerization of terminal acetylenes and terminal propargylic alcohols, ethers, and amides results mostly in the formation of two isomers favouring the head‐to‐tail derivatives.